Integrating herbal medicine into mainstream healthcare in Ghana: clients' acceptability, perceptions and disclosure of use - Peter Agyei-Baffour; Agnes Kudolo; Dan Yedu Quansah; Daniel Boateng (BMC, 2017)
Abstract Background Although there are current efforts to integrate herbal medicine (HM) into mainstream healthcare in Ghana, there is paucity of empirical evidence on the acceptability and concurrent use of HM, in the formal health facilities in Ghana. This study sought to determine client perception, disclosure and acceptability of integrating herbal medicine in mainstream healthcare in Kumasi, Ghana. Methods A cross-sectional study was conducted from May to August, 2015. Five hundred patients presenting at the outpatient departments of Kumasi South, Suntreso and Tafo Government Hospitals in Kumasi were randomly selected. Interviews were conducted with the use of structured questionnaires. A logistic regression analysis, using backward selection, was conducted to determine the influence of socio-demographic and facility related factors on the odds of using HM at the facility. All statistical tests were two-sided and considered significant at a p-value of <0.05. Results Majority of the study respondents were females (64.8%) and the median age was 36 years. Less than half, 42.2%, of the respondents utilized HM services when they visited the health facility. Reasons for using HM at the facility level included 'being effective' (24.4%), 'easy to access' (25.3%) and 'being comparatively cheaper' (16%). About 86% never disclosed previous use of HM to their health care providers. Socio-economic status and perception of service provision influenced use of herbal medicines. Respondents who rated themselves wealthy had increased odds of using herbal medicines at the health facility as compared to those who rated themselves poor (OR = 4.9; 95%CI = 1.6-15.3). Conclusion This study shows that integration of herbal medicine is feasible and herbal medicines may be generally accepted as a formal source of healthcare in Ghana. The results of this study might serve as a basis for improvement and upscale of the herbal medicine integration programme in Ghana.